Students' Attitudes towards Internet Memes in Writing Descriptive Text - Ulil Albab Adha; Yanti Sri Rezeki; Syarif Husin; Eni Rosnija; Eka Fajar Rahmani (Universitas Muhammadiyah Kalimantan Timur, 2023)
The aim of this research is to investigate students’ attitudes in writing descriptive text using Internet memes as a writing medium and the reasons leading to the particular attitude that occurred. This qualitative descriptive research was conducted using purposive sampling to a class that consists of 13 fourth semester students of the English Language Education study program at Universitas Tanjungpura in Essay Writing course. There are two types of data collected in this research; they are primary and secondary data. The primary data were obtained from the semantic differential questionnaire and the semi-structured interview, which was conducted to five of the students, whereas the secondary data were acquired from students’ writing scores of the Internet memes descriptive writing task. The findings reported that students have a positive attitude towards the task of writing descriptive text using Internet memes. Factors that influenced their positive attitude are the sense of enjoyment and casual feeling from the task, the sense of freedom and relatedness from their chosen memes, and the visual aid from the pictures that helps illustrate better description and helps them understand how to describe better in words. From the result, it is clear that the Internet memes pictures are helpful to boost their attitudes in writing descriptive text. It is suggested that by using fun writing media, such as Internet memes, writing teachers can put students in a comfortable learning atmosphere, so that they can absorb other important learning materials better.